2016
DOI: 10.1089/mdr.2015.0083
|View full text |Cite
|
Sign up to set email alerts
|

blaNDM-1 Carriage on IncR Plasmid in Enterobacteriaceae Strains

Abstract: Four NDM-1-producing Enterobacteriaceae strains (three Klebsiella pneumoniae and one Citrobacter koseri) were isolated between 2009 and 2011 through a nationwide surveillance for carbapenem-resistant Enterobacteriaceae in Croatia to study the molecular genetic background of blaNDM and the responsible plasmid types. Phenotypically, the clinical strains proved to be multidrug resistant. All strains remained susceptible to tigecycline and colistin. The clinical strains harbored variable antibiotic resistance dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…The 46-kb pTRE-1611 genome (KX863570) has a putative IncR replicon and 39 open reading frames. Although IncR plasmid replicons were first described in Salmonella strains ( García-Fernández et al, 2009 ), they have since been more commonly found in Klebsiella pneumoniae (e.g., Compain et al, 2014 ), and are often associated with the epidemic metallo-β-lactamase NDM-1 (e.g., Kocsis et al, 2016 ). IncR replicons are characteristically non-conjugative.…”
Section: Resultsmentioning
confidence: 99%
“…The 46-kb pTRE-1611 genome (KX863570) has a putative IncR replicon and 39 open reading frames. Although IncR plasmid replicons were first described in Salmonella strains ( García-Fernández et al, 2009 ), they have since been more commonly found in Klebsiella pneumoniae (e.g., Compain et al, 2014 ), and are often associated with the epidemic metallo-β-lactamase NDM-1 (e.g., Kocsis et al, 2016 ). IncR replicons are characteristically non-conjugative.…”
Section: Resultsmentioning
confidence: 99%
“…Although bla NDM has been found on bacterial chromosomes (82)(83)(84), the vast majority of carriage occurs on plasmids, which play a vital role in dissemination. bla NDM has been reported to be carried on plasmids with a variety of replicon types (33,82,(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). There are a total of 355 bla NDM -carrying plasmids with complete sequences available in GenBank (accessed on 8 January 2018) (see Data Set S2 in the supplemental material).…”
Section: Plasmids Carrying Bla Ndmmentioning
confidence: 99%
“…16S rRNA methyl transferases responsible for high resistance to antibiotics were reported in bla NDM-1 positive Pseudomonas aeruginosa isolates in co-association with rmtC and rmtF genes on the chromosome [45]. IncR plasmid carrying bla NDM-1 was also reported in Citrobacter koseri acting as a reservoir for multidrug resistance [46]. bla NDM-1 was associated with different plasmid scaffolds (IncFII, IncL/M, IncN, IncR, IncHIB-M/FIB-M), IncF type being the prevalent one.…”
Section: Introductionmentioning
confidence: 99%